2004
DOI: 10.1103/physrevb.69.014424
|View full text |Cite
|
Sign up to set email alerts
|

Spin-glass phase of cuprates

Abstract: We investigate a phenomenological model for the spin glass phase of La_{2-x}Sr_xCuO_4, in which it is assumed that holes doped into the CuO_2 planes localize near their Sr dopant, where they cause a dipolar frustration of the antiferromagnetic environment. In absence of long-range antiferromagnetic order, the spin system can reduce frustration, and also its free energy, by forming a state with an ordered orientation of the dipole moments, which leads to the appearance of spiral spin correlations. To investigat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
78
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(82 citation statements)
references
References 63 publications
(119 reference statements)
4
78
0
Order By: Relevance
“…This phase was recently the subject of a theoretical study [39] that suggested the origin was based upon localized topological defects (termed "solitonic spin liquid") derived from a combined Mössbauer and theoretical analysis. The localized topological defects have parallels with proposed structures for the spin-glass phase in the lamellar cuprates [40].…”
Section: Introductionmentioning
confidence: 71%
“…This phase was recently the subject of a theoretical study [39] that suggested the origin was based upon localized topological defects (termed "solitonic spin liquid") derived from a combined Mössbauer and theoretical analysis. The localized topological defects have parallels with proposed structures for the spin-glass phase in the lamellar cuprates [40].…”
Section: Introductionmentioning
confidence: 71%
“…6), by taking into consideration a small additional frustrating effect of the local Zn impurity that slightly reduces the effective coupling. Also localized holes give rise to a frustration, 55 in this case of dipolar nature, that is often indicated as the cause of the dramatic reduction of T N (h). Our m F (h) data in Fig.…”
Section: B Nature Of the Two Magnetically Ordered Regimesmentioning
confidence: 99%
“…In addition to its pedagogical value, this section contains explicit results that should be useful for analyzing STM experiments on quasi 1D systems with dilute impurities, such as the chain-layers 4 Recent reviews of the mechanisms of stripe formation in the cuprates and, more generally in doped antiferromagnets, often with rather different perspectives on the issue, can be found in Refs. (Carlson et al, 2003;Emery et al, 1999;Hasselmann et al, 2002;Ichioka and Machida, 1999;Vojta and Sachdev, 1999;White et al, 2002;White and Scalapino, 2000;Zaanen, 1998;Zaanen and Littlewood, 1994). 5 Various perspectives concerning the relevance of local stripe order to other properties of the high-temperature superconductor are reviewed in (Carlson et al, 2003;Castro Neto, 2001;Lorenzana et al, 2001a,b;Zaanen et al, 2001).…”
Section: Introductionmentioning
confidence: 99%